Enhancing physical fitness through Crossfit for 15-16-year-old high school students - Igor Vypasniak; Olena Nesen; Marina Jagiello (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. CrossFit represents a high-intensity functional training that has recently gained popularity among the youth. At the same time, restrictions imposed by military actions require different approaches to organizing CrossFit sessions. The most acceptable solution in such a situation is online education and training. The purpose of this study was to investigate the impact of CrossFit sessions within the framework of remote physical education on the physical fitness indicators of high school students.